Literature Review: Intervensi Prone Positioning Dalam Pengelolaan Pasien dengan Acute Respiratory Distress Syndrome - Etika Emaliyawati; Titin Sutini; Ermiati Ermiati; Asep Solehudin; Firman Sugiharto; Restuning Widiasih (Malahayati Nursing Journal, 2024)
ABSTRACT Acute Respiratory Distress Syndrome (ARDS) is one of the causes of most patients being admitted to the Intensive Care Unit (ICU) and has the potential to cause death due to inadequate gas exchange due to fluid in the alveoli. One of the interventions given is prone positioning to increase lung expansion. This study examines the benefits and impact of prone positioning intervention in ARDS patients. This literature review uses the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines with the keywords "ARDS, effectiveness, and prone positioning" using the Science Direct, PubMed, and Google Scholar databases. The inclusion criteria were full text in English or Indonesian with no restriction a publication year. 4,164 articles were collected according to keywords, and five articles that had gone through elimination and met the inclusion criteria were selected. Prone positioning in ARDS patients can reduce mortality and increase PaO2/FiO2. However, there are drawbacks, such as causing pressure ulcers in certain areas and does not reduce the potential complications of VAP. Prone positioning benefits patients by reducing mortality and increasing PaO2/FIO2. In practice, prone positioning must be supported by the presence of trained medical personnel, and possible complications must be reduced. Keywords: ARDS, Effectiveness, Prone Positioning  ABSTRAK ARDS atau Acute Respiratory Disstress Syndrom merupakan salah satu penyebab kebanyakan pasien masuk Intensive Care Unit (ICU) dan berpotensi menyebabkan kematian sebab pertukaran gas inadekuat akibat cairan di alveolus, salah satu intervensi yang diberikan adalah prone positioning untuk meningkatkan ekspansi paru. Penelitian ini bertujuan untuk melihat manfaat dan dampak dari intervensi prone positioning pada pasien ARDS. Literature review ini menggunakan panduaan Preferred Reporting Items for Systematic Reviews (PRISMA) dengan kata kunci “ARDS, efektivitas, dan prone positioning”dengan menggunakan database Science Direct, PubMed, dan GoogleSchollar. Kriteria inkluasi yaitu fulltext berbahasa Inggris atau Indonesia dan tidak ada retrisksi tahun publikasi. Terkumpul 4.164 artikel sesuai dengan kata kunci dan terpilih 5 artikel yang telah melalui eliminasi dan sesuai dengan kriteria inklusi. Prone posisitioning pada pasien ARDS dapat mengurangi angka kematian dan meningkatkan PaO2/FiO2, meskipun terdapat kekurangan seperti mengakibatkan pressure ulcer di bagian tertentu dan tidak mengurangi potensikomplikasi VAP. Prone positioning bermanfaat untukpasien sebab mengurangi angka kematian dan meningkatkan PaO2/FIO2. Dalam praktiknya, prone positioning harus ditunjang dengan kehadiran tenaga medis terlatih, dan mengurangi komplikasi yang mungkin terjadi. Kata Kunci: ARDS, Efektivitas, Prone Positioning